SYMBOLISM DISCUSSION OF THE ANGELS AND DEMONS MOVIE - Jimmi; Sidauruk, Juniato (Universitas Wiralodra, 2020)
This research focuses on symbolism which is appeared in Angels and Demos movie. There are various symbolisms shown through this Angels and Demons movie. Most of the symbolism has different meaning to be analyzed. The discussion covers on symbolism specifically on types and meaning on it. This research uses qualitative-description research which is accomplished by the writer by getting the data needed through this movie, having the library and internet research with the relevant sources, collects the data to be analyzed also describing meaning by explaining the result of the research. The conclusion of the research is finding five types of symbolism whereas only three symbolisms are suitable for this research, discover the meaning of every single symbolism found.